2021
DOI: 10.2147/copd.s325419
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Stenotrophomonas maltophilia When Detected in Sputum of Ambulatory Patients with COPD

Abstract: Introduction:Stenotrophomonas maltophilia is an emerging Gram-negative MDR bacteria. In patients with chronic obstructive pulmonary disease (COPD), it is mostly found in those with severe exacerbation of COPD requiring mechanical ventilation. The significance of S. maltophilia when detected in the sputum of ambulatory patients with COPD is uncertain. Objective: To access the prevalence and the risk factors of the presence of S. maltophilia in the sputum of ambulatory patients with COPD and to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“… 18 In a Canadian population of outpatients with COPD, S. maltophilia was detected in 10% of patients and associated with a twofold increase in mortality. 19 In a recent study from our group, S. maltophilia in the lower respiratory tract was associated with a threefold increased risk of both hospitalisation-requiring exacerbation of COPD and death. 20 …”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“… 18 In a Canadian population of outpatients with COPD, S. maltophilia was detected in 10% of patients and associated with a twofold increase in mortality. 19 In a recent study from our group, S. maltophilia in the lower respiratory tract was associated with a threefold increased risk of both hospitalisation-requiring exacerbation of COPD and death. 20 …”
Section: Introductionmentioning
confidence: 85%
“…The evidence on COPD and the role of S. maltophilia is sparse, and even slimmer when considering ICS use in patients with COPD. A single study has found an association between ICS and infection with S. maltophilia , but not differentiated by ICS doses 19. A meta-analysis covering eight studies on S. maltophilia in intensive care units shows an association between COPD and S. maltophilia pneumonia 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical epidemiology of the emerging NFGNB from recent studies is summarized in Table 1[45,46,61,70,72–97].…”
Section: Infections In Immunocompromised Hostmentioning
confidence: 99%
“…In a Canadian population of COPD outpatients, S. maltophilia was found in 10% of patients, and associated with a 2-fold increase in mortality [ 6 ]. However, the sample size was small (n = 397), and the prevalence was notably higher than earlier findings of 0.5% in stable COPD patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%